LITERATURE REVIEW : RASIO KEUANGAN PADA PERBANKAN KONVENSIONAL DI INDONESIA - Selvi Marni putri Selvi; Rahma Beva Nopiana; Levia Roza (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2024)
Financial ratios are analytical tools used to convey the financial performance of a company or business entity. Therefore, this research aims to find out how much influence CAR, NIM and BOPO have on banking profitability. The technique used in this research uses the Systematic Literature Review (SLR) method. In this research, the articles obtained were 30 Sinta indexed articles for being published between 2020-2024. Sinta journal articles were analyzed. The findings showed that the CAR and BOPO variables had an effect on profitability, whereas the NIM variable had no effect and not significant to Profitability. Keywords: Financial Ratios, CAR, NIM, BOPO, Profitability